2017
DOI: 10.1002/ente.201600688
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Neural Network Modeling of Partial Uptake for a Carbon Dioxide/Methane/Water Ternary Mixture on 13X Zeolite

Abstract: In this work, GERG2008 EoS embedded in a volumetric–gravimetric technique was utilized to measure multicomponent partial uptakes into the mixture. The sophisticated combination may overlap recent theoretical measurements and replace it with real‐time and experimental selective adsorption analysis. 13X zeolite was utilized as a solid adsorbent for the adsorption of binary and ternary CO2/CH4/H2O mixtures. Premixed and preloaded water vapor was studied at 323 K temperature and up to 10 bar pressure. The isotherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 54 publications
(18 citation statements)
references
References 92 publications
(176 reference statements)
0
18
0
Order By: Relevance
“…In binary mixtures, competitive adsorption is a controlling factor that usually takes place for between the adsorbate species on the solid surface. This phenomena shows that the adsorption of both adsorbates on the solid surface occurs with certain fractional loadings [47] . A revisited mathematical equation was proposed by Kurniawan et al [51] for and for a binary adsorption predictions as shown in the following equations (Eqs.…”
Section: Binary Modelling Predictionmentioning
confidence: 73%
See 3 more Smart Citations
“…In binary mixtures, competitive adsorption is a controlling factor that usually takes place for between the adsorbate species on the solid surface. This phenomena shows that the adsorption of both adsorbates on the solid surface occurs with certain fractional loadings [47] . A revisited mathematical equation was proposed by Kurniawan et al [51] for and for a binary adsorption predictions as shown in the following equations (Eqs.…”
Section: Binary Modelling Predictionmentioning
confidence: 73%
“…Where and are the amounts of APG and AEC adsorbed on the rock surface, respectively, that are calculated directly from pure experimental data [47] .…”
Section: Selectivity Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…A feedforward back‐propagation neural network (FFBP) is considered one of the most applied learning algorithms as it moves forward with the data sets in hidden layers, composed of artificial functional neurons. The algorithm predicts outcomes according to the provided experimental data, checks for errors, and repeats the process with a different number of neurons and network weights, to minimize mean square errors (MSEs) …”
Section: Introductionmentioning
confidence: 99%